Metal Organic Frameworks Loaded Polymeric Membranes in Pervaporative Desalination Applications: A Mini Review - Derya Unlu (Journal of Innovative Science and Engineering, 2021)
Pervaporative desalination is an efficacious method to obtain fresh water from saline water sources. High salt rejection and capacity to cope with high-salt concentration water solutions are important advantages of pervaporation process. To improve pervaporative desalination performance, researches concentrate on novel membrane types. Water stable metal organic frameworks loaded membranes attract substantial attention among novelty membrane applications. This study focuses on pervaporative desalination with MOF loaded polymeric membrane. First of all, the features of MOFs, synthe sis methods, usage areas are explained. Then, MOFs loaded mixed matrix membranes, production methods, used MOF types in membranes and applications in pervaporative desalination are examined. At the end of the study, future expectation on the desalination applications of MOF loaded membranes are presented as concluding remarks. Metal organic framework loaded polymeric membranes are seen as promising candidates to obtain drinking water with high separation yield in pervaporative desalination pro ess.